Single 8-oxo-guanine and 8-oxo-adenine lesions induce marked changes in the backbone structure of a 25-base DNA strand - Malins, Donald C. (The National Academy of Sciences, 2000)
Structural changes in a 25-base DNA strand, induced by single 8-oxo-guanine or 8-oxo-adenine substitutions, were shown by using Fourier transform-infrared spectroscopy with multivariate statistics. Pronounced differences were demonstrated between the parent and derivatives with respect to base interactions and changes in the phospho-deoxyribose backbone. The greatest degree of change in the backbone likely occurred immediately adjacent to the 8-oxo group, potentially altering the stereochemistry at a distance. The 8-oxo lesions, formed from reactive oxygen species (e.g., hydroxyl radicals), may appreciably alter the conformational properties of strands at the replication fork, thus affecting the selectivity of polymerases, the proofreading capability of repair enzymes, and the fidelity of the transcriptional machinery.